Serial changes in left ventricular myocardial deformation in sepsis or septic shock using three-dimensional and two-dimensional speckle tracking echocardiography - Yan, Xiaojun; Li, Yuman; Liu, Juanjuan; Zhou, Ting; Zhou, Yi; Sun, Wei; Sun, Chenchen; Ma, Jing; Zhang, Li; Shang, You; Xie, Mingxing (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to investigate the serial changes in left ventricular (LV) myocardial deformation in patients with sepsis using three-dimensional (3D) and two-dimensional (2D) speckle tracking echocardiography (STE). Methods In this single-center, prospective, and observational study, we included 59 patients diagnosed with sepsis or septic shock in the intensive care unit and 40 healthy controls. Left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (GLS), and global circumferential strain (GCS) assessed by 3D STE and 2D STE were obtained on the first, third, fifth, seventh to the tenth day after sepsis or septic shock. Results In patients with sepsis or septic shock, 3D and 2D LVEF were not different at each time point. GLS and GCS obtained by 3D STE and 2D STE decreased on the first day compared with the healthy group (all P < 0.01). Compared with the values on the first day, GLS and GCS further decreased on the third day, while 3D and 2D LVEF did not differ. 3D and 2D STE strains were lowest on the third day and gradually improved on the seventh to the tenth day compared with values on the third day. When compared with values on the first day, 3D and 2D GLS gradually improved on the seventh to the tenth day, whereas 3D and 2D GCS on the seventh to the tenth day was not different. Although 3D and 2D STE strains were significantly increased on the seventh to the tenth day, they were not fully recovered to normality. Conclusion Although patients with sepsis or septic shock demonstrated gradual improvements in 3D and 2D STE parameters during the ten-day period, LV myocardial strain was not fully recovered to normality by the seventh to the tenth days. 3D and 2D strain imaging, used as a helpful tool for monitoring the evolution of myocardial deformation, can provide clinicians with a useful additional imaging parameter.